2012
DOI: 10.1088/0004-637x/750/2/107
|View full text |Cite
|
Sign up to set email alerts
|

On the Origin of the Angular Momentum Properties of Gas and Dark Matter in Galactic Halos and Its Implications

Abstract: We perform a set of non-radiative hydrodynamical simulations of merging spherical halos in order to understand the angular momentum (AM) properties of the galactic halos seen in cosmological simulations. The universal shape of AM distributions seen in simulations is found to be generically produced as a result of mergers. The universal shape is such that it has an excess of low AM material and hence cannot explain the exponential structure of disk galaxies. A resolution to this is suggested by the spatial dist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
41
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 88 publications
(156 reference statements)
8
41
2
Order By: Relevance
“…The inner and outer parts of their DM halos are less aligned, indicating that major merging events are contributing to the buildup of spheroidal galaxies. This is in line with previous studies showing that major mergers with misaligned spins can be responsible for angular momentum misalignments (Sharma et al 2012). …”
Section: The Alignment Of the Host Halos With Their Centerssupporting
confidence: 93%
See 1 more Smart Citation
“…The inner and outer parts of their DM halos are less aligned, indicating that major merging events are contributing to the buildup of spheroidal galaxies. This is in line with previous studies showing that major mergers with misaligned spins can be responsible for angular momentum misalignments (Sharma et al 2012). …”
Section: The Alignment Of the Host Halos With Their Centerssupporting
confidence: 93%
“…This is due to the fact that within the halo the stars are more concentrated toward the center, whereas the spin of the DM component is dominated by the outer part of the halo, where most of the angular momentum of the DM component resides, as also shown in the right panel of Figure 22 inAppendix C. In addition, major mergers result in a reduction of the specific angular momentum, as shown in Welker et al (2014). On the contrary, the gas component always has a spin parameter distribution shifted toward larger values, in agreement with more recent studies by Sharma & Steinmetz (2005), Kimm et al (2011), Sharma et al (2012, and Danovich et al (2015), but in contrast to previous studies by van den Bosch et al (2002) and Chen et al (2003), who found nearly the same spin distributions for gas and DM. The larger spin values for the gas reflect the continuous transport of the larger angular momentum from the outer parts into the center due to gas cooling.…”
Section: The Spin Parameter λsupporting
confidence: 89%
“…This suggests that, in general, galaxy mergers might not decrease the angular momentum of the stellar component, but merely redistribute it to larger radii. This inside-out transport of angular momentum had already been observed for DM (Zavala, Okamoto & Frenk 2008;Sharma, Steinmetz & Bland-Hawthorn 2012). Fig.…”
Section: Appendix B: Galaxy Morphology and Stellar Angular Momentumsupporting
confidence: 76%
“…Another possibility, proposed by Roškar et al (2010), is misaligned angular momentum of in-falling gas. How the angular momentum of halo gas becomes misaligned is described in Sharma et al (2012). However, Aumer & White (2013) and Sales et al (2012) suggest that misaligned gas can destroy the disks.…”
Section: Introductionmentioning
confidence: 99%